Love in Translation: Analyzing Chapman’s Five Love Languages and Cultural Adaptation in Irish Wish - Arbain; Sacko, Makan (English Department, Universitas Negeri Surabaya, 2025)
Romantic films play a pivotal role in shaping global perceptions of love, yet little is known about how emotional expressions are adapted across cultures through translation. This study explores the intersection of Chapman’s Five Love Languages and translation strategies in the Indonesian subtitling of Irish Wish. Using a qualitative case study, 110 dialogues were purposively sampled from the official Netflix subtitles. Dialogues were classified into love language categories (Chapman, 2009) and analyzed through Molina and Albir’s (2002) translation framework. AntConc software assisted in text pattern identification, while expert validation ensured coding reliability. Findings reveal Words of Affirmation (75.45%) as the most dominant love language, followed by Acts of Service (15.45%), with minimal presence of Gifts, Quality Time, and Physical Touch. Literal translation, modulation, and established equivalents emerged as the most frequently applied strategies, supported by selective use of adaptation, reduction, and borrowing to maintain emotional nuance. The study highlights how translators balance linguistic fidelity and cultural resonance, ensuring emotional authenticity in Indonesian contexts. By integrating relationship psychology with translation studies, this research contributes to media localization scholarship and underscores the importance of culturally adaptive subtitling for cross-cultural empathy.